Interactions and Evolution of the Greenland Ice Sheet Surface Mass Balance with the Global Climate - Sellevold, R. (author) (2021)
One of the major consequences of ongoing global warming is the melting of the Greenland ice sheet (GrIS). The GrIS, as the world’s second largest freshwater reservoir, has the potential to raise sea levels by 7.4 m (Bamber et al., 2018a,b). Such a sea level rise would have a devastating effect on coastal societies, where a large fraction of the world’s population lives. Therefore, constraining the GrIS’ contribution to sea level rise is an important and vital task to plan for the future efficiently. Since the 1990s, the GrIS has been losing mass at an accelerated rate (Enderlin et al., 2014; Bamber et al., 2018a; Shepherd et al., 2019; Oppenheimer et al., 2019). We can separate GrIS mass loss into the contribution from the surface mass balance (SMB) and ice discharge. The SMB is the primary contributor to recent GrIS mass loss (van den Broeke et al., 2016); thus, there is a need for accurate projec tions of GrIS SMB, and a thorough understanding of physical processes governing the surface mass loss under global warming. Further, the GrIS also interacts with the climate system (Fyke et al., 2018), highlighting the need for coupled global climate projections. This thesis’ primary targets are to 1. Investigate the coevolution of the GrIS SMB and the global climate under increased greenhouse gases. 2. Examine the impact of reduced Arctic sea ice on GrIS SMB 3. Make projections of future GrIS surface melt. This is achieved by using the Community Earth System Model (CESM) version 2.1 (Danabasoglu et al., 2020). CESM2 is a newly developed coupled earth system model that features an online downscaling of the SMB through elevation classes (ECs), advanced snow physics (van Kampenhout et al., 2017), and a prognostic calculation of snow albedo (Flanner and Zender, 2006). Also, the EC simulated SMB is interactive; that is, modification of surface fluxes of mass and energy is communicated to the earth system’s other components. This thesis presents analysis of some of the first simulations of Greenland ice sheet climate ...